Movement behaviour in adults with haemophilia compared to healthy adults. Issue 3 (1st March 2018) - Timmer, M. A.; Pisters, M. F.; de Kleijn, P.; de Bie, R. A.; Schutgens, R. E. G.; Veenhof, C.
Abstract : Background: Limited research has been published regarding movement behaviour of adult persons with haemophilia (PWH). It is hypothesized that avoidance of activities and more sedentary behaviour cause poorer physical functioning. Aim: To determine differences in movement behaviour between PWH and healthy adults. Methods: Movement behaviour was measured with an accelerometer distinguishing between; lying/non‐wear, sitting, standing, walking, running and cycling. Time spent on activities was compared between PWH and healthy adults, using absolute time spent on activities and activities as percentage of wear time. Results: One hundred and five PWH (32 mild/moderate with a mean age of 42.8 ± 15.1, severe 42.1 ± 13.6) and 98 healthy adults (mean age 41.9 ± 15.5) showed that adults with severe haemophilia sit and stand more than healthy adults (4.5 [CI 0.6‐8.4] and 4.2 [CI 1.8‐6.6] h/wk, respectively) and walk and run less (3.4 [CI 1.4‐5.3] hours and 33.6 [CI 19.0‐41.7] min/wk, respectively). Patients with mild/moderate haemophilia stand more than healthy adults (3.3 [CI 0.1‐6.4] h/wk). Differences in sitting between severe haemophilia and healthy adults and differences in standing between mild/moderate haemophilia and healthy adults disappeared when using activities as percentage of wear time. Conclusion: Movement behaviour of adults with severe haemophilia differs from healthy adults, mainly due to less walking and less running. No differences were found in other activities and postures or the distribution of movement behaviour over the day. No significant differences were found between adults with mild/moderate haemophilia and healthy adults.